Sistem Kelayakan Borang Akreditasi Program Studi Menggunakan Fuzzy Inference System - Yanto Hermawan; Irman Hermadi; Heru Sukoco (Forum Dosen Indonesia, 2020)
The Board of National Accreditation Body for Higher Education) evaluates the performance of a study program. This compels it to improve and maintain its performance. The process of accreditation involves several steps, one of which is the completion of accreditation documents by the study program. The completion requires data from various sources, both from the study program and the institution. However, the data required are often not recorded properly and kept by different sources. As a result, it takes longer time to complete the arrangement. Moreover, inconsistent data format becomes another factor which holds back this process. The application of fuzzy inference system, as used by Kesatuan Business and Informatics Institute, as in the above case can result in a better scoring in which each component is assessed and it will yield the prediction of the expected accreditation status before it is submitted to BAN-PT. This research aims to develop a web based accreditation system with fuzzy inference system and construct a prediction of score ad accreditation status in IBI Kesatuan, using 4 variables of input assessment criteria, namely: external condition, institutional profile, criteria and analysis, and development program decision. The resulting output is the status of non- accredited, good accredited, excellent accredited, and superior accredited. There are 4 phases in the methods: problem identification, needs and system analysis, system design, system implementation and testing system. The result of blackbox test show that 8 features can operate well. The features consist of criteria menu, indicator menu, date user, LKPS data, LED data, LKPS and LED assessment input, recapitulation and conclusion. Based on the results of the study, it can be concluded that accreditation system can be applied to predict the scores and accreditation status of information system study program of IBI Kesatuan. Keywords: accreditation, fuzzy inference system